Soils with hardened laterites are they really high P-sorbing? - López-Hernández, Danilo (Ciencia, 2017)
In well weathered tropical soils, a common feature of the environment is the presence of laterite within the soil profile. The soils with laterites are considered agriculturally poor because of many major agro-management-related problems such irreversibility hardening upon exposure and phosphorus fixation. In those soils, amorphous and crystalline forms of Fe and Al are the main responsible for P-sorbing sites; however adsorption tends to decrease as long as the amorphous forms are aged. In thiscontribution, fourteen tropical soil series (or sites) which differ according with the presence of hardened laterites in the profile, were compared for P-sorption and associated soil properties. It was found that P-sorption was lower in the case of the soil with hardened laterite none-the-less that the laterite presented a higher amount of free iron in the subsoil. Basically, lateritic soils sorb less P than the non-lateritic ones probably because the clay fraction is diluted by coarse laterite fragments that due to the cementation of their mineral grains and their low porosity present a small surface area for P sorption. The results have important agroecological implications since laterite soils are abundant in sub and tropical regions and commonly are ascribed as high P-sorbing materials.